Peningkatan Kreativitas Anak Usia Dini Melalui Metode Percobaan Sains Sederhana dengan Kegiatan Ecoprint: Peningkatan Kreativitas - Yunesti, Dilla (ICEJ : Islamic Childhood Education Journal, 2023)
Creativity is essential for children’s lives, but it is still found that 8 out of 12 children have not developed creativity abilities. It can be seen from the children who are still fixated on what the teacher and friends are doing. The children are not yet able to recognize textures. The children are not able to make various shapes. Therefore this study aims to analyze the application of simple science experiment methods with ecoprint activities to early childhood creativity. The research approach used is quantitative with the type of research Quasi Experiment Design type Nonequivalent Control Group. The sample in this study was 12 children, 6 children as the experimental group and 6 children as the control group. The data collection techniques used were descriptive statistical analysis and nonparametric statistical analysis. The data analysis results in an effect of the simple science experiment method with ecoprint activities on the creativity of children aged 5-6 years. It was concluded that a simple science experiment method with ecoprint activities could increase children’s creativity. This research implies that the application of simple science experiment methods with ecoprint activities can develop children’s creativity.